Estudio descriptivo de reacciones adversas y problemas relacionados al medicamento por Palibizumab reportadas al Programa Distrital de Farmacovigilancia Bogotá D.C 2014 –2016 (2017)
A descriptive study was carried out based on the reports submitted to the District Pharmacovigilance Program of Bogotá in 2014-2016 in order to establish the prevalence of adverse events and related problems in the reported cases of the 655 cases presented by the district program of pharmacovigilance, the exclusion of 13 cases was carried out in duplicate, leaving a total of 642 cases, using variables such as: age, sex, type of report (Suspected Adverse Drug Reaction and Problems Related to Drugs), causality, outcome negative associated with medication, definitions of the pharmacovigilance program according to the World Health Organization, INVIMA. Of the 642 cases analyzed, it was observed that Respiratory Syncytial Virus occurs in 56 of the confirmatory cases and the remaining cases related to lower respiratory tract diseases or general alterations. We classified 609 cases for SRAM and 7 cases for PRM, the rest were classified as not applicable because they are pathologies of non-relational origin with the drug. The age group is classified by age from 0 months to 28 months; being representative ages from 0 to 6 for having an immunological disability by classifying as newborn pretermins; The PRMs identified respond to noncompliance of the therapy by the EPS, erroneous administration, prescription errors, corresponding to 5 cases and the NOM associated with need as an untreated health problem and quantitative ineffectiveness for two reports. In the system / organ classification, there is a relationship with the representation of cases of alterations of the respiratory system with the whoat-sub due to signs of bronchiolitis, pneumonia, cough, nasal congestion